Fundamental food microbiology - Ray, Bibek (CRC Press, 2008)
"Maintaining the high standard set by the previous bestselling editions, Fundamental Food Microbiology, Fourth Edition presents up-to-date information in this rapidly growing and highly dynamic field. Revised and expanded to reflect recent advances, this edition broadens coverage of foodborne diseases to include many new and emerging pathogens, as well as descriptions of the mechanism pathogenesis. An entirely new